A Novel AP2/ERF Transcription Factor, OsRPH1, Negatively Regulates Plant Height in Rice - Ma, Ziming; Wu, Tao; Huang, Kai; Jin, Yong-Mei; Li, Zhao; Chen, Mojun; Yun, Sokyong; Zhang, Hongjia; Yang, Xue; Chen, Haoyuan; Bai, Huijiao; Du, Lin; et al. (Frontiers in Plant Science, 2020)
The APETALA 2/ethylene response factors (AP2/ERF) are widespread in the plant kingdom and play essential roles in regulating plant growth and development as well as defense responses. In this study, a novel rice AP2/ERF transcription factor gene, OsRPH1, was isolated and functionally characterized. OsRPH1 falls into group-IVa of the AP2/ERF family. OsRPH1 protein was found to be localized in the nucleus and possessed transcriptional activity. Overexpression of OsRPH1 resulted in a decrease in plant height and length of internode and leaf sheath as well as other abnormal characters in rice. The length of the second leaf sheath of OsRPH1-overexpressing (OE) plants recovered to that of Kitaake (non-transgenic recipient) in response to exogenous gibberellin A3 (GA3) application. The expression of GA biosynthesis genes (OsGA20ox1–OsGA20ox4, OsGA3ox1, and OsGA3ox2) was significantly downregulated, whereas that of GA inactivation genes (OsGA2ox7, OsGA2ox9, and OsGA2ox10) was significantly upregulated in OsRPH1-OE plants. Endogenous bioactive GA contents significantly decreased in OsRPH1-OE plants. OsRPH1 interacted with a blue light receptor, OsCRY1b, in a blue light-dependent manner. Taken together, our results demonstrate that rice RPH1 negatively regulates plant height and bioactive GA content by controlling the expression of GA metabolism genes. OsRPH1 is involved in blue light inhibition of leaf sheath elongation by interacting with OsCRY1b.